Outcome of Modified Weis Procedure Versus Jones Procedure in Senile Entropion at Tertiary Eye Centre of Western Nepal - Manandhar, Laxmi Devi; Shrestha, Koshal; Bhattarai, Binita; Kharel, Ramita (Journal of Nepalgunj Medical College, 2024)
Introduction: Involutional lower eyelid entropion is a common condition of eyelid that affects ageing population. Various surgical procedures have been described for correction of involutional entropion of the lower eyelid that addresses one or more of the anatomical factors.Aims: This study evaluate the success rate, recurrence, and postoperative complications between the two procedures modified Weis versus Jones procedure for involutional lower lid entropion.Methods: A prospective, cross section- al study. All patients with senile entropion who met the inclusion criteria were randomly divided into Group A (modified Weis group) and Group B Jones group Patients were evaluated on the 1st and 14 postoperative day and followed up at 6 months. The surgical outcomes were normal eyelid position at rest, recurrence and complications of surgery.Results: 59 patients (64 eyelids) with involutional entropion that met the inclusion criteria underwent surgical repair. Left eyelid (29) was more involved than the right eye (25). 5 patients had bilateral entropion repair. There were no major intraoperative complications except bleeding which occurred in 8 eyelids (12.5%). Postoperative period was uneventful. The success rate of Modified Weis procedure at 6 months was 93.7% whereas it was 100% in Jones procedure. The success rate was same at 3 months and 6 months duration.Conclusion: The functional and surgical outcome for involutional entropion with either transconjunctival modified Weis approach or external Jones approach was same. But Jones procedure has comparatively high success rate and minimal or no recurrence.